Vegetation biodiversity response to excessive flooding in permanent and ephemeral wetlands - Genrich, Connor (University of Wisconsin--Stout. Office of Research and Sponsored Programs, 2017)
Ephemeral wetlands vary greatly in water depth and animal diversity in a highly dynamic habitat. The vegetation response of these wetlands to flooding in comparison to their more permanent counterparts is poorly understood. Increased precipitation resulted in a significant mean wetland water level increase in 2014 compared to 2013. In both these years, we surveyed vegetation in 24 permanent and 33 ephemeral wetlands in the Chippewa Moraine region of Wisconsin. In general, cover, species richness, and Shannon and Simpson diversity indices were all significantly higher in permanent wetlands than ephemeral ponds. After one year of extensive flooding, we observed a loss of both species richness and cover in both ephemeral and permanent wetlands. Ephemeral wetlands exhibited slightly more biodiversity loss from flooding than permanent wetlands, although these differences were not significant. These results suggest wetland vegetation is affected by flooding. Our study provides a baseline of information for studies exploring future environment change.
Research article with graphs.
Keywords: ephemeral; flooding; wetland; Wetlands; Plant communities; Vernal pools; Plants--Effect of floods on; Floods